Start With a Joke: Humor, Presenter’s Status, Gender, and Investment Level - Abira Reizer; Yael Brender-Ilan (SAGE Open)
While previous work suggested that presenters may benefit from the use of humor, others argue that the use of humor can be risky. Therefore, there is a need to examine the potential moderators and mediators of this process. The study aims to experimentally explore the appropriate use of humor during a professional investment presentation. The sample included 400 participants. After being randomly assigned to 2 × 2 between-subjects conditions (man /woman presenter × with/without a humorous message), the participants watched a video of an investment presentation. Participants who were asked to invest virtual money in the firm after the video. Using a moderated mediation analysis, the results show that humor was related to higher investment amounts and that the presenters’ perceived organizational status mediated this indirect relationship. The novelty of the study lies in its experimental design, focusing on audience behavioral tendencies and its unexplored mixed-gender effect: women tended to invest less when a male presenter used humor, while men tended to invest more when a female presenter used humor. The perceived status of the presenter mediated these associations. Theoretically, the study expands the understanding of the Benign Violation Theory (BVT) regarding the need to address contextual factors while examining the appropriate use of humor. Moreover, to maximize the benefits of humor, one must consider the humor’s relevance to the audience and acknowledge that humor needs to be appropriately used. This is particularly important for people working in investment settings.